Corporate Restructuring and Management Buyouts in Asia-Pacific and Europe - Koh, Winston T. H. (Institutional Knowledge at Singapore Management University, 2005)
This paper reviews some of the recent trends of the buyout sector in the private equity industry in the Asia-Pacific and Europe, and introduces the contributions to this special issue of the Journal of Restructuring Finance